Antioxidant and α-glucosidase inhibitory activities of eight neglected fruit extracts and UHPLC-MS/MS profile of the active extracts - Mohamed Yunus, Siti Norhamimah; Abas, Faridah; Jaafar, Ahmad Haniff; Azizan, Awanis; Zolkeflee, Nur Khaleeda Zulaikha; Abd Ghafar, Siti Zulaikha (Springer, 2021)
The 70% ethanolic extracts from eight neglected fruits; Muntingia calabura, Leucaena leucocephala, Spondias dulcis, Syzygium jambos, Mangifera caesia, Ardisia elliptica, Cynometra cauliflora and Ficus auriculata were evaluated for their 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging, α-glucosidase inhibitory activities as well as total phenolic content. The results of this study revealed that M. caesia fruit extract demonstrated the most potent radical scavenging activity. Among the fruits examined for α-glucosidase inhibitory activity, M. calabura and F. auriculata exhibited strong activity with no significant difference. The Pearson correlation indicated that the activities of M. caesia and F. auriculata contributed by phenolic compounds. A total of 65 metabolites were tentatively identified by using ultra-high-performance liquid chromatography tandem mass spectrometry (UHLPC-MS/MS). These findings suggested that the possible application of M. caesia and F. auriculata as a functional food with antioxidant and α-glucosidase inhibitory properties.